A Quantum Chemistry Approach to Possible Sulfur Adsorbate Structures on the Basal Plane of Graphite Clusters - Vicente, José Luis (1996)
A quantum chemistry study for possible sulfur adsorbate structures on the basal plane of graphite clusters has beenmade using the MNDO method. The potential energy curves showed the possible formation of S atoms, sulfur dimer and trimer adsorbates on top and bridge substrate positions, whereas neither sulfur atom, dimer, nor trimer adsorption binding to hollow position could be formed. Results gave support to a recently reported interpretation for sulfur atom adsorption on the basal plane of graphite based upon scanning tunneling microscopy data.